2010
DOI: 10.1016/j.ijid.2010.02.2268
|View full text |Cite
|
Sign up to set email alerts
|

Welders are at increased risk for invasive pneumococcal disease

Abstract: Welders, particularly those who smoke, are at increased risk of IPD and should be considered for routine administration of the pneumococcal polysaccharide vaccine. Ongoing workplace measures to reduce exposure to metal fumes and promote smoking cessation should be reinforced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 11 publications
1
48
0
Order By: Relevance
“…2,4,24 We focused on S pneumoniae because this bacterium is the most common cause of community-acquired pneumonia in adults. 10 In addition, a review of all patients presenting with invasive pneumococcal disease (IPD) in Alberta (Canada) from 2000 to 2004 by Wong et al 25 reported a 2.7-fold greater incidence of IPD in welders; of the 18 welders with IPD, 17 had bacteremic pneumococcal pneumonia, 1 had meningitis, and 1 died of pneumococcal infection. Pneumococcal infection in welders remains a problem.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,24 We focused on S pneumoniae because this bacterium is the most common cause of community-acquired pneumonia in adults. 10 In addition, a review of all patients presenting with invasive pneumococcal disease (IPD) in Alberta (Canada) from 2000 to 2004 by Wong et al 25 reported a 2.7-fold greater incidence of IPD in welders; of the 18 welders with IPD, 17 had bacteremic pneumococcal pneumonia, 1 had meningitis, and 1 died of pneumococcal infection. Pneumococcal infection in welders remains a problem.…”
Section: Discussionmentioning
confidence: 99%
“…4 Unarguably, respiratory diseases encompass some of the communicable and non-communicable leading causes of death worldwide; while industrialization is enhancing the phenomenon of increased risk, especially in urban areas. [5][6][7] Tobacco smoke remains a controversial subject, but also unarguably a risk factor. The need for clinical toxicity testing has been advocated, not-with-standing that haematological and haemorrheological changes possibly associated with cigarette smoking have long been speculated.…”
Section: Issues Of Management and Monitoring By Laboratory Methods Inmentioning
confidence: 99%
“…4 Similar reports relating to lobar and pneumococcal infection in welders subsequently emerged from Sweden 5 and Canada. 6 pathway and now enrols all their students in the MBBS programme with the option of undertaking research during their course, leading to a master's degree, with the potential to expand this for the few who have the aptitude and ability to do so. 3 In summary, encouraging highperforming students to enrol in a combined professional and research medical degree can only be a sustainable way to develop skilled clinician scientists if postgraduate pathways to academic medicine are clearly defined.…”
Section: Community-acquired Pneumonia and Weldingmentioning
confidence: 99%